A REPRESENTAÇÃO DAS EMPREGADAS DOMÉSTICAS EM SOLITÁRIA, DE ELIANA ALVES CRUZ, SOB A ÓTICA EPISTEMOLÓGICA NEGRA E DECOLONIAL - COSTA, Larissa de Menezes (2026)
The general objective of this research is to investigate the representations of domestic workers in contemporary Black Brazilian literature, based on the novel "Solitária" (2022) by Eliana Alves Cruz, analyzing it from the perspective of the intersectionality of gender, race, and social class within the context of domestic work. Specifically, we will examine how the work represents a Black and decolonial epistemology through the representations of domestic workers, citing Black characters such as Eunice and Mabel. Finally, we will examine the impacts of this representation of domestic workers and their treatment in contemporary narratives in the post-slavery context. The methodology is basic and intersectional, preceded by a literature review, characterized as qualitative critical analysis. To this end, we draw on discussions by Gaston Bachelard (1993) on space; Halbwachs (2013) on memory; Coloniality and Decoloniality based on María Lugones (2020), Aníbal Quijano (2005), Nelson MaldonadoTorres (2018); from the perspective of resistance discussed by Alfredo Bosi (2002) and the discussions on race and social class by Beatriz Nascimento (2021), bell hooks (2019a, 2024b) and Djamila Ribeiro (2018). From the perspective of Black-Brazilian literature, theorists such as Cuti (2010), Fernanda Miranda (2019), Miriam Alves (2010), Mirian dos Santos (2018), Eduardo de Assis Duarte (2011), among others, have highlighted. Therefore, based on a decolonial analysis focusing on the representation of domestic workers, we attempt to demonstrate how these characters can problematize their daily lives and subvert dominant logics, as well as the transformative potential of contemporary Black-Brazilian literature as an instrument of resistance, denunciation, and (re)construction of other epistemologies.